Detailed statistical analysis plan for the target temperature management after out-of-hospital cardiac arrest trial - Nielsen, Niklas (BioMed Central, 2013)
BACKGROUND: Animal experimental studies and previous randomized trials suggest an improvement in mortality and neurological function with temperature regulation to hypothermia after cardiac arrest. According to a systematic review, previous trials were small, had a risk of bias, evaluated select populations, and did not treat hyperthermia in the control groups. The optimal target temperature management (TTM) strategy is not known. To prevent outcome reporting bias, selective reporting and data-driven results, we present the a priori defined detailed statistical analysis plan as an update to the previously published outline of the design and rationale for the TTM trial. METHODS: The TTM trial is an investigator-initiated, multicenter, international, randomized, parallel-group, and assessor-blinded clinical trial of temperature management in 950 adult unconscious patients resuscitated after out-of-hospital cardiac arrest of a presumed cardiac cause. The patients are randomized to a TTM of either 33°C or 36°C after return of spontaneous circulation. The primary outcome is all-cause mortality at maximal follow-up (until end of the trial and a minimum of 180 days). The main secondary outcomes are the composite outcome of all-cause mortality and poor neurological function (Cerebral Performance Category (CPC) 3 and 4, and modified Rankin Scale (mRS) 4 and 5) at hospital discharge and at 180 days; and assessment of safety and harm: bleeding, infections, electrolyte and metabolic disorders, seizures, cardiac arrhythmia, and renal replacement therapy. CONCLUSION: The TTM trial investigates potential benefit and harm of two target temperature strategies, both avoiding hyperthermia in a large proportion of the out-of-hospital cardiac arrest population. TRIAL REGISTRATION: ClinicalTrials.gov identifier: NCT01020916